Inhibition mechanism of interaction effect between charged character of inhibitor and rare earth elements for Mg-Gd-Y alloy. (January 2023) - Cui, Yanan; Yang, Zhice; Zhang, Tao; Wang, Fuhui
Abstract: The inhibition mechanism of four inhibitors with different charge on Mg-Gd-Y alloy was investigated experimentally and theoretically. The different charge of inhibitor evoked the preferential adsorption behavior, changing the susceptibility of Mg-Gd-Y alloy to micro-galvanic corrosion. Moreover, the adsorption of inhibitor changed the surface energy of embryos of corrosion product, and strongly suppressed the nucleation rate of corrosion product, leading to poor protective performance. Thus, the inhibitor with anion, exhibiting satisfactory inhibition efficiency for AZ/AM series alloys, showed worse inhibition for the Mg-Gd-Y alloy. Finally, the strategy to select and/or synthesize inhibitors for Mg-RE alloys was presented. Highlights: Inhibitor changed the alloy's susceptibility to micro-galvanic corrosion. Inhibitor with anion weakened the induction effect of multi-stage nucleation. Inhibition effect of anion inhibitor on AZ/AM Mg alloy is better than Mg-Gd-Y alloy. The strategy to select and/or synthesize inhibitors for Mg-RE alloys was presented.